2020
DOI: 10.48550/arxiv.2012.03107
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

When Do Curricula Work?

Xiaoxia Wu,
Ethan Dyer,
Behnam Neyshabur

Abstract: Inspired by human learning, researchers have proposed ordering examples during training based on their difficulty. Both curriculum learning, exposing a network to easier examples early in training, and anti-curriculum learning, showing the most difficult examples first, have been suggested as improvements to the standard i.i.d. training. In this work, we set out to investigate the relative benefits of ordered learning.We first investigate the implicit curricula resulting from architectural and optimization bia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 28 publications
3
8
0
Order By: Relevance
“…We compared popular CL methods on a large number of datasets and deep learning architectures in the text and image domains, and we found that current CL methods do not increase success much, in line with the results of studies [4,11] recently published in the literature. Almost all of the methods in the literature increase the size of the dataset [3,4,6].…”
Section: Introductionsupporting
confidence: 81%
See 3 more Smart Citations
“…We compared popular CL methods on a large number of datasets and deep learning architectures in the text and image domains, and we found that current CL methods do not increase success much, in line with the results of studies [4,11] recently published in the literature. Almost all of the methods in the literature increase the size of the dataset [3,4,6].…”
Section: Introductionsupporting
confidence: 81%
“…In [11], Extensive experiments were conducted on curriculum learning and examined the situations in which curriculum methods work. Curriculum, Anti-Curriculum, and Random-Curriculum methods were compared.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Our goal is to define metrics to detect underrepresented data regions during the training. In supervised learning, training dynamics-the behavior of a model as training progresses-have been used to detect "hard-to-learn" samples (Chang et al, 2017;Swayamdipta et al, 2020;Wu et al, 2020a).…”
Section: New Metrics To Diagnose Gan Trainingmentioning
confidence: 99%